Hemoglobin Differences in Uncomplicated Monochorionic Twins in Relation to Birth Order and Mode of Delivery. (14th April 2016) - Verbeek, Lianne; Zhao, Depeng P.; te Pas, Arjan B.; Middeldorp, Johanna M.; Hooper, Stuart B.; Oepkes, Dick; Lopriore, Enrico
Abstract : Aim: To determine the differences in hemoglobin (Hb) levels in the first 2 days after birth in uncomplicated monochorionic twins in relation to birth order and mode of delivery. Methods: All consecutive uncomplicated monochorionic pregnancies with two live-born twins delivered at our center were included in this retrospective study. We recorded Hb levels at birth and on day 2, and analyzed Hb levels in association with birth order, mode of delivery, and time interval between delivery of twin 1 and 2. Results: A total of 290 monochorionic twin pairs were analyzed, including 171 (59%) twins delivered vaginally and 119 (41%) twins born by cesarean section (CS). In twins delivered vaginally, mean Hb levels at birth and on day 2 were significantly higher in second-born twins compared to first-born twins: 17.8 versus 16.1 g/dL and 18.0 versus 14.8 g/dL, respectively ( p < .01). Polycythemia was detected more often in second-born twins (12%, 20/166) compared to first-born twins (1%, 2/166; p < .01). Hb differences within twin pairs delivered by CS were not statistically or clinically significant. We found no association between inter-twin delivery time intervals and Hb differences. Conclusions: Second-born twins after vaginal delivery have higher Hb levels and more often polycythemia than their co-twin, but not when born by CS.